Comparison of SVPWM, SPWM and HCC Control Techniques in Power Control of PMSG used in Wind Turbine Systems - Suleyman, Naim; Yasa, Yusuf; Aksoy, Ismail; Sahin, Yakup (IEEE, 2015)
In this paper, the performance of space vector pulse width modulation (SVPWM), sinusoidal pulse width modulation (SPWM) and hysteresis current control (HCC) control techniques used in power control with back to back converter of permanent magnet synchronous generator used in wind turbines are comparatively analyzed in terms of dynamic response, total harmonic distortion (THD), torque ripple and current ripple. Furthermore, SVPWM and SPWM are compared in terms of the using DC link voltage. Analysis of system is realized with MATLAB/Simulink program. There is not paper that together of these three control techniques are compared in terms of common results or values in literature. Permanent magnet synchronous generator (PMSG) is used in simulations is surface mounted, bipolar and its power is 1.8 kW. However, PMSM's energy transmission to grid is made with Field Oriented Control (FOC). According to analysis results, it has been observed that SVPWM generally has more efficient results than both HCC and SPWM control technique. Also, it is observed that SVPWM can produce about 15 percent higher than SPWM in output voltage.
Keywords: Field oriented control; PMSG; back to back converter; space vector pulse width modulation; hysteresis control; Engineering